PENERAPAN PRINSIP-PRINSIP GREEN EKONOMI BAGI USAHA TANI BERKELANJUTAN - Ary Tamtama; Sitti Rahma Ma'mun; Rosmawaty Rosmawaty (Jurnal Abdi Insani, 2023)
Puosu Jaya Village is located in Konda Sub District, South Konawe Regency, Southeast Sulawesi Province with the majority of the villagers working as farmer. Due to intensive farming, the village has experienced declining in soil fertility. Over the years, this problem has resulted in low productivity. Low productivity is also faced by fish farmers due to high price of fish feed. To help farmers dealing with the problem Community Empowerment by Students or PMM program aims to impove farmers' knowledge and skills on organic farming through training and innovation. The program included training on organic farming, composting and liquid organic fertilizer, organic fish feed, and silk worm (Tubifex sp.) for fish fry feed. Composting and green pesticide were produce using biomass in surrounding area and manure, while fish feed was prepared using tofu pulp and fish powder. All ingredients were cheap and available locally. The implementation of activities is focused on the demonstration plot location in Hamlet I, Puosu Jaya Village. Methods for implementing activities include demonstrations of organic cultivation, training in making fertilizers, pesticides and organic feed as well as training in cultivating silk worms as the main food for catfish seeds. The target group is the people of Puosu Jaya Village who work as farmers and fish cultivators. The results obtained were (1) the production of demonstration plots for organic plants, catfish cultivation and silk worm cultivation (2) facilitated efforts to increase community knowledge and skills in cultivating food crops using organic fertilizers and vegetable pesticides.